The idea of building “ an ecological community with a shared future”reflected in the paintings of “Xin’an School” (Journal of Global Arts Studies, 2024)
Background: As an important cultural symbol in Anhui Province of China, the paintings of Xin'an School contain rich ecological philosophy, especially the concept of building "an ecological community with a shared future." Objective: Through analyzing the representative paintings of the Xinan School, the article tries to explore the concept of "an ecological community with a shared future" expressed by artists. Methods: First, the paper focuses on the development of the idea of "an ecological community with a shared future." Secondly, the paper summarizes the previous research of Xin'an Painting School. Then, the article analyzes the concept of "an ecological community with a shared future" reflected in the works of Xin'an School of painting. Results: For Xin'an School painters, all things in nature have one destiny. Therefore, we should love nature, treat animals equally and advocate the harmonious coexistence of human beings, animals, plants, etc. In addition, harmonious social and ecological relations are crucial to the sustainable development of human beings. Because of this, Xin'an School painters think of constructing a harmonious social ecological community through the cultivation of self-spiritual ecology. Conclusion: The ecological concepts reflected in the paintings of the Xin'an School have important implications. First, human beings should establish consciousness of the natural ecological community. Second, we should stop the destruction of nature at once. Third, the study is beneficial in solving the global ecological crisis. Finally, the construction of an ecologically harmonious society cannot be separated from everyone's efforts.
Keywords: Xin’an School; Paintings; “An ecological community with a shared future”; Ecological implications